2017
DOI: 10.36108/njsa/7102/51(0190)
|View full text |Cite
|
Sign up to set email alerts
|

Youth Unemployment and Electoral Malpractices in Nigeria

Abstract: In Nigeria, elections have been marred by various forms of malpractices in which youth often play prominent roles. The economic crisis and the accompanying structural adjustments in Nigeria have resulted in the alienation and marginalization of the youth, thereby exacerbating the whole phenomenon of youth restiveness. The National Bureau of Statistics reported that 42.24% of Nigerian youths were unemployed and 15.2 million youths remain unemployed in the economy in 2016. This unemployment scenario heightens th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…For the three levels of poverty P1, P2, and P3, unemployment rate (UR) has a positive and a significant effect on the poverty rate. The findings are in line with the results presented by Meo et al ( 2018 ), Oduwole ( 2015 ), Gallie et al ( 2003 ), Meo et al ( 2018 ), Ukpere and Slabbert ( 2009 ), Saunders ( 2002 ), and Martínez et al ( 2001 ), who conclude that unemployment is one of the major underlying factors behind poverty and they found the positive and significant association between them, while our result contradicts the results of Gustafsson and Johansson ( 1999 ) where poverty had no relationship with unemployment. According to International Labor Organization (ILO), nearly 90% of workers living in extreme poverty are in sub-Saharan African countries.…”
Section: Model Estimation and Resultssupporting
confidence: 93%
“…For the three levels of poverty P1, P2, and P3, unemployment rate (UR) has a positive and a significant effect on the poverty rate. The findings are in line with the results presented by Meo et al ( 2018 ), Oduwole ( 2015 ), Gallie et al ( 2003 ), Meo et al ( 2018 ), Ukpere and Slabbert ( 2009 ), Saunders ( 2002 ), and Martínez et al ( 2001 ), who conclude that unemployment is one of the major underlying factors behind poverty and they found the positive and significant association between them, while our result contradicts the results of Gustafsson and Johansson ( 1999 ) where poverty had no relationship with unemployment. According to International Labor Organization (ILO), nearly 90% of workers living in extreme poverty are in sub-Saharan African countries.…”
Section: Model Estimation and Resultssupporting
confidence: 93%
“…Poverty and unemployment both have become, at present, a contemporary challenge of social existence for human beings worldwide. Oduwole (2015) explored the relationship between unemployment and poverty through content analysis. He further identified that these issues have deep down roots in poor governance, leadership and security.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Oduwole (2015) explored the relationship between unemployment and poverty through content analysis. He further identified that these issues have deep down roots in poor governance, leadership and security.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The majority (83%) of the respondents were below the age of 20, while 15.6% were between the ages of 20%, 24%, and 0.7% were aged 25 to 29, and 0.7% were 35 and older. According to Nigeria's National Youth Policy (2001) (Oduwole, 2015), the age range for the youth in Nigeria is 18 to 35. Thus, 99.03% of the participants were classified as youth.…”
Section: Methodsmentioning
confidence: 99%